2020
DOI: 10.1111/apps.12279
|View full text |Cite
|
Sign up to set email alerts
|

Is Grit Hurting You? The Dark Side of Psychological Resources in Goal Pursuit

Abstract: This article presents a study of the curvilinear role of psychological resources during goal striving through an interactive model linking work goal progress to a valued resource. Specifically, we explore the nonlinear relationship of grit with work goal progress. Additionally, we test the moderating role of perceived organizational support (POS) for this relationship. We hypothesized that an employee’s goal pursuit is not merely contingent on the excessive availability of the selected resources but instead mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 71 publications
(84 reference statements)
2
17
0
Order By: Relevance
“…This study confirmed that grit is associated with higher OP based on data analysis. We also found how two potential moderators (i.e., SC and TL) can strengthen the relationship between grit and OP; however, there has been limited research on the role of grit in performance (Credé et al, 2017;Khan et al, 2020). To be specific, when the organization consists of gritty employees, it is likely to show a higher performance level.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…This study confirmed that grit is associated with higher OP based on data analysis. We also found how two potential moderators (i.e., SC and TL) can strengthen the relationship between grit and OP; however, there has been limited research on the role of grit in performance (Credé et al, 2017;Khan et al, 2020). To be specific, when the organization consists of gritty employees, it is likely to show a higher performance level.…”
Section: Discussionmentioning
confidence: 67%
“…This study contributes to the literature by suggesting the requisite personal traits for tough times (Rego et al, 2021 ). Third, while the importance and effectiveness of grit have been studied, little attention has been paid to contingency and the expression of grit (Credé et al, 2017 ; Jordan et al, 2019 ; Choi et al, 2020 ; Khan et al, 2020 ). Therefore, this study adds to the literature by looking at how grit can be expressed based on organizational climate and leadership.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…COR theory states that personal resources, such as grit, allow employees to be better equipped to pursue their goals and attain personal growth (Khan et al, 2021;Xanthopoulou et al, 2009;Wang et al, 2020). Gritty employees are perseverant and passionate, so their robust interest and efforts to chase their initial goals and thrive in the workplace is evident (Duckworth & Quinn, 2009;Ramasamy & Mun, 2017).…”
Section: Job Insecurity and Gritmentioning
confidence: 99%
“…Although engaging in grit requires spending resources, its benefits on the worker's performance and behavior in the workplace exceed its costs (Jordan et al, 2018). One of the main benefits is that grit is a personal resource that inspires employees to maintain their pursuit of their goals when enduring obstacles and hardships (Khan et al, 2021;Sinclair, 2017). In other words, grit is considered a "general resistance resource" that influences how people identify and approach potential stressors, such as JI (Jin & Kim, 2017;Jordan et al, 2018).…”
Section: Moderating Effect Of Gritmentioning
confidence: 99%